Hubungan Dukungan Sosial dan Pemberitaan Media dengan Kecemasan Ibu Menjalani Kehamilan Masa Pandemi COVID-19 di Kota Medan Tahun 2020 - Hutahaean, Masta Melati; Wahyu, Afnizar (Jurnal Riset Hesti Medan, 2021)
Maternal Mortality Rate (MMR) is one indicator to see the success of maternal health efforts. Since WHO officially declared the corona virus outbreak (COVID-19) as a pandemic. The COVID-19 pandemic has hit almost all countries in the world and has an impact on various health and non-health sectors. It is undeniable that this condition will cause maternal anxiety during pregnancy. The sampling technique in this study was carried out by the quota sampling technique. Analyzed by chi-square test. The results of the study on the relationship between social support and maternal anxiety during pregnancy showed that there was a relationship between social support and maternal anxiety during pregnancy (p value 0.003) with an OR of 3.187 which means that pregnant women with good social support have an estimated chance of 3.187 times experiencing mild anxiety levels. compared to pregnant women with less social support. In addition, the results of the study show that there is a relationship between media coverage and maternal anxiety during pregnancy (p value < 0.001) with an OR of 4.56 which means that pregnant women who are exposed to positive media coverage have an estimated 4.56 times chance of experiencing mild anxiety levels compared to those who are exposed to positive media coverage. pregnant women with negative media coverage. It can be concluded that social support and media coverage have been shown to be associated with maternal anxiety during pregnancy during the COVID-19 pandemic. It is recommended for health workers to be able to adapt to health services that are adapted to health protocols that focus on efforts to promote health, prevent disease and empower pregnant women. Although visits to health facilities are only prioritized for pregnant women who have problems, health workers are still required to be able to innovate in developing education for pregnant women with various media that can be reached by all pregnant women.